(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background Legumes, scientifically classified as Fabaceae or Leguminosae, constitute the third most extensive family of flowering plants, surpassed only by (Orchidaceae) and asters (Asteraceae). The genus Vicia faba L., which is temperate and herbaceous in nature, belongs to the legume tribe Vicieae of the Papilionoideae. Legumes and cereals are the two most important flowering plants used in agriculture. Legumes are useful as human and animal food, and as soil-improving components of agricultural and agroforestry systems. Materials and methods The present study involved the extraction of DNA from the foliage of the Vicia faba L plant, followed by its amplification using three primers for the purpose of conducting ISSR analysis by polymerase chain reaction (PCR). Results This process resulted in the generation of a total of 30 DNA fragments, which were then able to be assessed across all genotypes. The aggregate count of polymorphic markers and the mean percentage of polymorphism were recorded as 43.33%. Conclusion The findings of our study indicate a substantial degree of genetic diversity within the fenugreek treatments. This discovery also suggests that the ISSR technique provides more comprehensive information for assessing genetic diversity and connections among populations of Vicia faba L.